Biometria de sementes, morfologia de plântulas e crescimento inicial de cinco espécies frutíferas que ocorrem no Nordeste brasileiro - Silva, Tatiana Maria da (2014)
Brazilian native fruits are among the most tasty and nutritious in the world, being known only by the local population. The knowledge of the morphology of seeds and seedlings is useful in understanding the development of native species, being fundamental in the study of germination in species identification in the juvenile stage, the interpretation of tests of germination and differentiation of congeners. The study of the initial growth of plants is important for establishing standards of seedlings produced in nurseries. The objective of this work was to obtain information on biometrics seed, seedling morphology and early growth of American ximenia L, Genipa americana L., Ziziphus joazeiro Mart., Talisia esculenta Raldk and Crataeva tapia L. The experiments were conducted at the Center for Teaching and Research in Urban Agriculture (NEPAU), Department of Plant Science in CCA / UFC, Fortaleza-CE. Biometrics seeds was performed on a sample of 100 diaspores of each species. To study the morphology of seedlings made up planting 100 seeds in tubes of 288cm ³ s filled with vermiculite and humus in the volume ratio 2:1, except Juazeiro whose endocarps previously scarified, were sown in beds tire containing 2 offish 1 humus (v/v). We carried out daily photographic records of germination and seedling establishment process. The initial growth analysis was performed in two environments (full sun and greenhouse) during seven periods in a split plot design with six replications, in a randomized design, except for jujube plum mad and whose evaluations were performed only at home vegetation. The length values observed in ‘ameixa-brava’, ‘genipapo’, ‘juazeiro’, ‘pitomba’ and ‘trapiá’ were 14.98; 9.64; 8.74; 18.25 and 7.72 mm respectively. ‘Ameixa-brava’ and ‘pitomba’ presented hypogeal cryptocotyledonary germination, while the genipap ‘juazeiro’ and ‘trapiá’ and were characterized as phanerocotylar epigeal. Trapiá plants kept in the greenhouse showed better development. Seedlings ‘genipapo’ and ‘pitomba’ full sunlight exhibited greater development. The pattern of seedling plum mad at 109 days: 12.13 cm, 19.02 cm root length, 3.52 mm diameters and 7.1 leaves. The ‘juazeiro’ seedlings with 138 days exhibited the following pattern: height - 41.33 cm; root length - 37.84; stem diameter - 4.13 mm and number of leaves - 43.05.